2019
DOI: 10.15516/cje.v21i3.3177
|View full text |Cite
|
Sign up to set email alerts
|

The validity of student evaluation of teaching: Is there gender bias?

Abstract: Student evaluation of teaching (SET) has steadily, but surely, become an important assessment tool in higher education. Although SET provides feedback on students level of satisfaction with the course and the lecturer, the validity of its results has been questioned. After extensive studies, the factor which is believed to distort the SET results is gender of the lecturer. In this paper, Potthoff analysis is employed to additionally explore whether there is gender bias in SET. Namely, this analysis has been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Comments focused on female instructors' appearance and personality and demonstrated lower levels of professional respect compared to comments made about male instructors. Maricic et al (2019) found that student ratings of an instructors' clarity, professionalism, and objectivity were more important for male professors in predicting overall impressions, whereas nurturing qualities were emphasised for female professors. Moreover, male instructors were valued for demonstrating knowledge and expertise and female instructors for teaching methodology, providing clear explanations, and attitude Rodríguez et al, 2014).…”
Section: Types Of Biasmentioning
confidence: 91%
“…Comments focused on female instructors' appearance and personality and demonstrated lower levels of professional respect compared to comments made about male instructors. Maricic et al (2019) found that student ratings of an instructors' clarity, professionalism, and objectivity were more important for male professors in predicting overall impressions, whereas nurturing qualities were emphasised for female professors. Moreover, male instructors were valued for demonstrating knowledge and expertise and female instructors for teaching methodology, providing clear explanations, and attitude Rodríguez et al, 2014).…”
Section: Types Of Biasmentioning
confidence: 91%